Aberrant STYK1 expression in ovarian cancer tissues and cell lines - Jackson Kesmic A; Oprea Gabriela; Handy Jeffrey; Kimbro K Sean (BMC, 2009)
Abstract Background Overexpression of STYK1, a putative serine/threonine and tyrosine receptor protein kinase has been shown to confer tumorigenicity and metastatic potential to normal cells injected into nude mice. Mutation of a tyrosine residue in the catalytic STYK1 domain attenuates the tumorigenic potential of tumor cells in vivo, collectively, suggesting an oncogenic role for STYK1. Methods To investigate the role of STYK1 expression in ovarian cancer, a panel of normal, benign, and ovarian cancer tissues was evaluated for STYK1 immunoreactivity using STYK1 antibodies. In addition, mRNA levels were measured by reverse transcription PCR and real-time PCR of estrogen receptors, GPR30 and STYK1 following treatment of ovarian cell lines with estrogen or G1, a GPR30 agonist, as well as western analysis. Results Our data showed higher expression of STYK1 in cancer tissues versus normal or benign. Only normal or benign, and one cancer tissue were STYK1-negative. Moreover, benign and ovarian cancer cell lines expressed STYK1 as determined by RT-PCR. Estradiol treatment of these cells resulted in up- and down-regulation of STYK1 despite estrogen receptor status; whereas G-1, a GPR30-specific agonist, increased STYK1 mRNA levels higher than that of estradiol. Conclusion We conclude that STYK1 is expressed in ovarian cancer and is regulated by estrogen through a GPR30 hormone-signaling pathway, to the exclusion of estrogen receptor-alpha.